2021
DOI: 10.3389/ijph.2021.601591
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Multimorbidity Among Women Aged 15–49 Years in India: An Analysis of Prevalence, Patterns and Correlation

Abstract: Objectives: The present study has examined the patterns and possible correlates of coexisting morbidities among women aged 15–49 years based on biomarker measurement data at the national level in India.Methods: National Family Health Survey conducted during 2015–16 used in the present study. Simple disease count approach was used to calculate the multimorbidity among women. Multinomial logistic regression was applied to analyze the predictors of multimorbidity among women.Results: Almost 30% of the women had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
4
8
1
Order By: Relevance
“…However, after controlling for all other socioeconomic and demographic factors, no substantial caste difference in multimorbidity exists between rural and urban areas. Contrary to the other studies [29,[39][40][41], the present study shows that multimorbidity increases with an increase in education.…”
Section: Discussioncontrasting
confidence: 99%
“…However, after controlling for all other socioeconomic and demographic factors, no substantial caste difference in multimorbidity exists between rural and urban areas. Contrary to the other studies [29,[39][40][41], the present study shows that multimorbidity increases with an increase in education.…”
Section: Discussioncontrasting
confidence: 99%
“…But a cross-sectional study conducted in India reiterated caste as another social background characteristic to be significantly associated with multimorbidity. 18 Likewise, Puri et al ( 2021) study found that religion was related to multimorbidity. 17 We further found that alcohol (2015) study reveal that adults living in rural areas have a higher risk of multimorbidity than those living in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…We have considered socio-economic and demographic backgrounds characteristics in this study. The predictors that were considered in this analysis are age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), 50-59, 60-69, 70 years and above), marital status (never married, currently married/cohabiting, divorced/ separated/widowed), level of education (no formal education/less than primary/primary/secondary/higher secondary and above), place of residence (rural/urban), caste (Scheduled Tribes-ST/Scheduled Castes-SC/Other Backward Classes-OBC/Others), religion (Hindu/Muslim/ Others) of the respondents. Behavioral characteristics include alcohol consumption, physical activity, perceived loneliness, quality of life, and self-rated health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reporting some rise in life expectancy per decade does not necessarily indicate improved health scenario among women [ 4 ]. About 30% of the women had at least one chronic morbidity in India, and 9% had two or more morbidities [ 17 ]. When paired with reproductive and biological changes during childbearing ages, multimorbidity can lead to a declined quality of life and well-being [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%